Ritual Andingingi Cultur Kajang Ammatoa - Putri, Sarah Arsitha; Rahman, Abdul (Ridwan Institute, 2021)
This research and writing aims to find out the background of the implementation of the Andingingi Ritual as a custom of the Kajang Ammatoa tribe, Andingingi is a sacred ritual to facilitate the arrival of fortune, live long and be kept away from all harm. Based on the results of Andingingi's research, it means to cool the earth, almost all Kajaang tribesmen participated, from children to adults, this ritual was led by Labiria or Ammatoa representatives and traditional leaders of the Kajang tribe. During the ritual, participants are prohibited from talking and moving a lot because it can distract the attention of traditional stakeholders, before performing the ritual the community makes konre-konre (offerings) which are placed at various points. The Andingingi ritual is still being carried out today which causes an impact on the community, as can be seen from the socio-economic background and cultural tourism. This study uses a historical research method consisting of four stages, namely: heuristics (collection of data or sources) Criticism (sources consisting of internal and external criticism, interpretation or interpretation of sources and historiography, namely historical writing. Ammatoa is considered very primitive and rejects the entry of Modernization